The structure and evaluation of educational research skills and accomplishments among rural teachers: Data from China - Feng, Luo; Yuxiang, Yao; Lihua, Qiu (Frontiers in Psychology, 2023)
The rural teachers’ educational research is highly valued and very important for their professional development and for the revitalization of rural education. This study explores the structure of rural teachers’ educational research (Study 1). Based on the results, the regional norm of Hunan province is formulated, and the discriminant criterion of rural teachers’ educational research is developed (Study 2). In Study 1, data from two samples of 892 Chinese rural teachers in compulsory education schools of Hunan Province (a representative province in central China) support the constructs of the instrument. Principal exploratory and confirmatory factor analyses of 33 items of rural teachers’ educational research self-rating scale identified a first-order model with three factors: educational research on carrying out basic educational activities (CEA), educational research on creating an educational community (CEC), and educational research on refining and popularizing educational theory (RPE). Based on the results of Study 1, in Study 2, the norm of rural teachers’ educational research is formulated based on the data of Hunan Province. This norm serves as the reference standard for evaluating the level of rural teachers’ educational research. The structure of rural teachers’ educational research is discussed, and suggestions for the formulation of education policies are provided.